Internal Organization Communication Patterns Affecting the Employees’ Work Efficiency at a Media Production Company in Bangkok - Nunuan, Phimchanok; Siriwonese, Tongfu (Journal of Management Science Nakhonratchasima University, 2024)
The objectives of the research were 1) to study the internal communication patterns of the employees at a private media production company in Bangkok 2) to study the work efficiency of the employees at a private media production company in Bangkok 3) to study the work efficiency of the employees based on the personal factors at a private media production company in Bangkok and 4) to study the internal organization communication patterns affecting the employees’ work efficiency at a private media production company in Bangkok. The sample group was included with 115 employees of a private media production company in Bangkok. The statistics for the analysis were Frequency distribution, Percentage, Mean, Standard Deviation, t-test, One-Way ANOVA and Multiple Regression Analysis. The results showed that 1) the internal organization communication pattern of the employees, at a private media production company in Bangkok, had an average of 4.14, which was at a high level 2) the work efficiency of the employees at a private media production company in Bangkok had an average of 4.23, which was the highest level 3) The employees of a private media production company, with different genders and job titles, had no difference in work efficiency. However, the employees of a private media production company, with different ages, education levels, and different work experiences, had differences in work efficiency and 4) Considering the internal organization communication patterns; Horizon or Cross-organization communication and Top-down communication affected the work efficiency of the employees at a private media production company in Bangkok.